Torso hemorrhage: noncompressible? never say never - Lian-Yang Zhang; Hua-Yu Zhang (European Journal of Medical Research, 2024)
Abstract Since limb bleeding has been well managed by extremity tourniquets, the management of exsanguinating torso hemorrhage (TH) has become a hot issue both in military and civilian medicine. Conventional hemostatic techniques are ineffective for managing traumatic bleeding of organs and vessels within the torso due to the anatomical features. The designation of noncompressible torso hemorrhage (NCTH) marks a significant step in investigating the injury mechanisms and developing effective methods for bleeding control. Special tourniquets such as abdominal aortic and junctional tourniquet and SAM junctional tourniquet designed for NCTH have been approved by FDA for clinical use. Combat ready clamp and junctional emergency treatment tool also exhibit potential for external NCTH control. In addition, resuscitative endovascular balloon occlusion of the aorta (REBOA) further provides an endovascular solution to alleviate the challenges of NCTH treatment. Notably, NCTH cognitive surveys have revealed that medical staff have deficiencies in understanding relevant concepts and treatment abilities. The stereotypical interpretation of NCTH naming, particularly the term noncompressible, is the root cause of this issue. This review discusses the dynamic relationship between TH and NCTH by tracing the development of external NCTH control techniques. The authors propose to further subdivide the existing NCTH into compressible torso hemorrhage and NCTH’ (noncompressible but REBOA controllable) based on whether hemostasis is available via external compression. Finally, due to the irreplaceability of special tourniquets during the prehospital stage, the authors emphasize the importance of a package program to improve the efficacy and safety of external NCTH control. This program includes the promotion of tourniquet redesign and hemostatic strategies, personnel reeducation, and complications prevention.